Optimizing the performance of renewable sources using virtual renewable power plants - Rodrigues, L. (2012)
The concept of “Virtual Renewable Power Plants - VRPP” enables several positive factors for the electric integration of Renewable Energy Sources (RES) and enables the optimization of its technical and economic performance by using the natural complementary of renewable resources availability. Moreover, the establishment of synergies between different RES contributes for the smoothing of time based fluctuation of the power delivered by the RES. The present work aims to identify the synergies between wind and photovoltaic (PV) plants, regarding their daily profiles complementarity and resource availability; as well as the technical and economic added value of a VRPP. Results show an increase of 5.3% in the capacity factor and 25% in the revenue when 2 MWp of PV are added to an 8 MW wind farm, and a potential benefit of 48% when adding a storage system of 2 MW (8 MWh), considering all infrastructural capacity limits. Moreover, the combined VRPP daily production profiles have a significantly higher correlation with the average daily load profile (0.82) than WTG (0.41) or PV (0.54) alone.